Explaining the experience of breastfeeding in women with gestational diabetes and designing and implementing an educational program based on planned behavior theory: a combined exploratory study protocol - Soltan Asghari; Sanaz Mollazadeh; Nahid Jahani shoorab; Smira Shahbazzadegan; Talat Khadivzadeh (BMC, 2024)
Abstract Background Gestational diabetes is a type of carbohydrate intolerance that is diagnosed for the first time during pregnancy. Researches have shown that gestational diabetes is associated with many negative prenatal and birth outcomes. Because of the complications such as infant death, several diabetics' mothers plan to stop breastfeeding. Research findings indicate a decrease in breastfeeding in mothers with gestational diabetes/ or contradictory tissues regarding the factors affecting the breastfeeding behavior of mothers with gestational diabetes and a special program to promote breastfeeding for these mothers based on the social and cultural conditions of Iranian society. The present study aims to design an interventional program with a mixed qualitative study based on the theory of planned behavior (PBT) to prevent the decrease of breastfeeding in diabetic mothers. Methods/design A mixed methods exploratory design will be used to conduct this study in 3 phases. The first phase (qualitative): The purpose of the first phase is to understand the experience of breastfeeding mothers who had gestational diabetes, which will be done using the directed content analysis method. The purposive sampling will be used on pregnant mothers with gestational diabetes 30-34 weeks and mothers with infants (up to 6 months) with a history of gestational diabetes. The second phase include designing and implementing an educational program based on the PBT: Education will be conducted based on the needs assessment of the qualitative phase, the opinions of the focus group, and the literature review, then the breastfeeding behavior will be measured using the survey tool of "breastfeeding drop". The third phase: Interventional quantitative phase: The sample size will be carried out by a pilot study, then a designed program as an educational intervention for teaching breastfeeding behavior based on the PBT for 30-34 weeks pregnant mothers with gestational diabetes will be implemented during 3-4 sessions and breastfeeding behavior will be evaluated after delivery. Discussion This is the first mixed-method study in Iran that led to implement an interventional program based on the theory of planned behavior. Because of the complications such as infant death, several diabetics' mothers plan to stop breastfeeding. We hope that the result of this research will be a step in solving breastfeeding problems in mothers with gestational diabetes.